Robust locomotor performance of squirrel monkeys (Saimiri boliviensis) in response to simulated changes in support diameter and compliance. Issue 5 (5th January 2022) - Schapker, Nicole M.; Chadwell, Brad A.; Young, Jesse W.
Abstract: Arboreal environments require overcoming navigational challenges not typically encountered in other terrestrial habitats. Supports are unevenly distributed and vary in diameter, orientation, and compliance. To better understand the strategies that arboreal animals use to maintain stability in this environment, laboratory researchers must endeavor to mimic those conditions. Here, we evaluate how squirrel monkeys ( Saimiri boliviensis ) adjust their locomotor mechanics in response to variation in support diameter and compliance. We used high‐speed cameras to film two juvenile female monkeys as they walked across poles of varying diameters (5, 2.5, and 1.25 cm). Poles were mounted on either a stiff wooden base ("stable" condition) or foam blocks ("compliant" condition). Six force transducers embedded within the pole trackway recorded substrate reaction forces during locomotion. We predicted that squirrel monkeys would walk more slowly on narrow and compliant supports and adopt more "compliant" gait mechanics, increasing stride lengths, duty factors, and an average number of limbs gripping the support, while the decreasing center of mass height, stride frequencies, and peak forces. We observed few significant adjustments to squirrel monkey locomotor kinematics in response to changes in either support diameter or compliance, and the changes we did observe were often tempered by interactions with locomotor speed. These results differ from a similar study of common marmosets (i.e., Callithrix jacchus, with relatively poor grasping abilities), where variation in diameter and compliance substantially impacted gait kinematics. Squirrel monkeys' strong grasping apparatus, long and mobile tails, and other adaptations for arboreal travel likely facilitate robust locomotor performance despite substrate precarity. Abstract : Gait mechanics were studied while squirrel monkeys ( Saimiri boliviensis ) crossed simulated arboreal supports that varied in diameter and level of compliance. Traces show the average resultant displacement of the compliant pole across a stride, with vertical lines indicating the timing of limb touchdown (TD) events for left (L) and right (R) forelimbs (F) and hindlimbs (H). Overall, decreasing diameter and increasing compliance had little effect on squirrel monkey gait mechanics. Grasping extremities, long tails, and other adaptations for arboreal travel permit high locomotor performance in the face of increasing substrate precarity. Highlights: Squirrel monkeys make few gait changes on supports that are narrower and more compliant. Grasping extremities, long tails, and other adaptations for arboreal travel permit high locomotor performance in the face of increasing substrate precarity.